Impact of some environmental parameters on phytoplankton diversity in the eastern Al-Hammer marsh / southern Iraq - Ebtehal M. Jaffer; Nida J. Al-Mousawi; Imad J. M Al-Shawi (مجلة بغداد للعلوم, 2023)
Biodiversity is one of the important biological factors in determining water quality and maintaining the ecological balance. In this study, there are 223 species of phytoplankton were identified, and they are as follows: 88 species of Bacillariophyta and were at 44%,70 species of Chlorophyta and they were at 29 %, 39 species of Cyanophyta and they were at 16 %, 12 species of Euglenozoa and they were at 4 %, four species of Miozoa and they were at 3 %, and, Phylum Charophyta and Ochrophyta were only eight and two species, respectively and both of them were at 2%. The common phytoplankton recorded in the sites studied include Nitzschia palea, Scenedesmus quadricauda, Oscillatoria princeps, and Peridinium bipes, These species recorded a significant positive correlation with Ec, Sio3, and WT. Phytoplankton including Gomphosphaeria semen-Vitis, Dicloster acuatus, Tetrastrum heteracanthum, and Dictyocha fibula, recorded a significant positive correlation with NO3, PO4, DO, and PH. Water temperature ranged between 14.200 -33.900 ºc in Al-Mansoury and Al-Sada respectively. Electrical conductivity ranged between 2.790 - 11.900 ms/cm in Al-Sada and Al-Mansoury respectively. PH ranged between7.750-8.600 in Al-Dawody and Al-Mansoury respectively. Dissolved Oxygen (DO) ranged between 5.950 -13.000 mg/l in Al-Dawody and Al-Mansoury respectively.WT recorded negative correlation with pH (r= - 0.591), NO3-2 (r= - 0.463) and DO (r= - 0.603). Nitrate ranged between 0.570-12.200 µg /l in Al- and Al-Sada respectively. Phosphate ranged between 0.003-0.154 µg/l, in Al-Dawody and Al-Mansoury respectively. Silicate ranged between 51.200- 198.600 µg /l in Al-Baraka and Al-Dawody respectively. Shannon - Weiner index (H`) ranged between 2.275- 3.162 in Al-Dawody and Al-Mansoury respectively. Simpson index ranged between 0.856-0.950 in AlMansoury and Al-Sada respectively, while the Evenness index was 0.514-0.933 in Al-Dawody and Al-Baraka respectively. Shannon- Weiner index (H`) recorded a significant positive correlation with the Simpson index .